Predicting Peaks and Troughs in Real House Prices - Rousová, Linda (OECD Publishing, 2011)
OECD work prior to the financial crisis suggested that real prices in several housing markets had become vulnerable to a change in financial and economic conditions, with the risk of a subsequent downturn becoming increasingly possible, as proved to be the case. With corrections in many, but not all, housing markets having now occurred, and, in some countries, prices having rebounded rapidly in the low interest rate environment, the issue of whether prices are now close to another turning point is again of considerable policy interest. As a means of addressing this issue, probit models have been estimated to provide an indication of possible peaks and troughs in real house prices in 2011 and 2012, using data for 20 OECD countries. Predictions based on these models have been reported in OECD Economic Outlook, No. 89 and this paper provides information on the methodology underpinning these predictions
Keywords: Economics